1990
DOI: 10.1007/bf00309887
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic and peptidergic nerve components of intramural ganglia in the rat heart

Abstract: Immunohistochemical properties of the terminal nerve network in the rat heart were assessed by use of the elution-restaining method. The colocalization of the enzymes involved in catecholamine synthesis (tyrosine hydroxylase--TH. dopamine-beta-hydroxylase--DBH) as well as the respective distributions of the neuropeptides associated with the adrenergic nervous system (neuropeptide tyrosine--NPY, C-terminal flanking peptide of neuropeptide Y--C-PON) were studied in series of serial sections throughout the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…For example, dopamine ␤-hydroxylase but not tyrosine hydroxylase immunoreactivity is found within rat cardiac ganglia near the sinoatrial node, 4 whereas dopamine ␤-hydroxylase and tyrosine hydroxylase immunoreactivity are found in ganglia near the atrioventricular node of guinea pigs. 5 Tyrosine hydroxylase-immunoreactive nerve fibers projecting through cardiac ganglia and varicosities adjacent to neurons also occur.…”
Section: Immunohistochemical and Histochemical Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, dopamine ␤-hydroxylase but not tyrosine hydroxylase immunoreactivity is found within rat cardiac ganglia near the sinoatrial node, 4 whereas dopamine ␤-hydroxylase and tyrosine hydroxylase immunoreactivity are found in ganglia near the atrioventricular node of guinea pigs. 5 Tyrosine hydroxylase-immunoreactive nerve fibers projecting through cardiac ganglia and varicosities adjacent to neurons also occur.…”
Section: Immunohistochemical and Histochemical Studiesmentioning
confidence: 99%
“…For example, early studies using histofluorescence techniques do not report catecholamines within neurons of rat or guinea pig cardiac ganglia. 18 Recently, however, key marker enzymes in catecholaminergic neurons, including tyrosine hydroxylase and dopamine ␤-hydroxylase, were found in rat 3,4 and guinea pig 1,5 cardiac ganglia. To the best of our knowledge, no studies examining the presence of phenylethanolamine-N-methyltransferase (PNMT, which synthesizes epinephrine), tryptophan hydroxylase (which synthesizes serotonin), and histidine decarboxylase (which synthesizes histamine) within cardiac ganglia exist in the literature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moravec et al [43] found that ganglionic cells in epicardial ganglia and around the terminal groove (sulcus terminalis) are negative to VIP and TH and immunopositive to NPY and DBH. On the other hand, the bodies of intramural ganglia located between the right and the left branch of the His bundle are highly immunoreactive to TH and DBH.…”
Section: Neurochemical Characteristic Of Cardiac Gangliamentioning
confidence: 99%